Studies on ballising as a process for manufacturing high precision low-cost cylindrical bores - 367743 Kalanithi Jayakumaran (Skudai : Universiti Teknologi Malaysia, 1997)
Thesis (Master of Engineering (Mechanical)) - Universiti Teknologi Malaysia, 1997